High temperature ferroelectric behaviour in α-MnO2 nanorods realised through enriched oxygen vacancy induced non-stoichiometry. Issue 42 (19th October 2017) - John, Reenu Elizabeth; Chandran, Anoop; George, Justin; Jose, Ajai; Jose, Gijo; Jose, Joshy; Unnikrishnan, N. V.; Thomas, Marykutty; George, K. C.
Abstract : Here, we observe high temperature ferroelectric behaviour in non-stoichiometric α-MnO2 nanorods due to combined effects of charge and orbital ordering. Abstract : Nanostructuring followed by incorporation of defect induced non-stoichiometry is an emerging field of prominence due to its capacity to introduce unprecedented properties in materials with potential applications. In this work, crystalline α-MnO2 nanorods are synthesised using a facile co-precipitation method to exhibit ferroelectric behaviour for the first time. The evolution mechanism of the nanorods is investigated using XRD, HRTEM and FTIR spectra, while their thermal stability is probed using TGA/DTA. The novel properties observed are the result of structural rearrangements sparked by electrons in mixed valence cations (Mn 3+ /Mn 4+ ). The high density of Jahn–Teller active Mn 3+ cations breaks the inversion symmetry in α-MnO2, thereby altering the atomic environment inducing distortion in the basic MnO6 octahedra. Since variable temperature XRD analysis confirms the phase stability of the crystal structure up to very high temperatures, the ferroelectric phase exhibited by the material below T c is an outcome of the combined effects of orbital ordering (OO) of the e g electron in Mn 3+ and charge ordering (CO) of Mn 3+ and Mn 4+ cations. This is confirmed by DSC analysis. The breakdown of the ferroelectric nature is identified to originate as a result of octahedral tilting as suggested by temperature-dependent Raman studies. Magnetic and electrical transport studies provide additional evidence of a CO ferroelectric phase as they predict the existence of double-exchange hopping conduction and surface ferromagnetism in the sample.